2018
DOI: 10.1101/471730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleepless and Desynchronized: Impaired Inter Trial Phase Coherence of Steady-State Potentials Following Sleep Deprivation

Abstract: The results suggest that the capability of the brain to synchronize with rhythmic stimuli is disrupted without sleep. Thus, decreased ITPC may represent an objective and mechanistic measure of sleep loss, allowing future work to study the relation between brain-world synchrony and the specific functional impairments associated with sleep deprivation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Unfortunately, most studies do not report whether or not there were responses at higher harmonics, as mentioned above. Moreover, when higher harmonic responses were reported to be present, they were often not described, for example, "Peaks were also present at the harmonics of the stimulus frequency but were not analyzed in this study" (Srinivasan et al, 1999, p. 5438); "Higher harmonics may play a role, especially at lower temporal frequencies (see, for example, the double peaks in the 12-Hz data in Figure 1), but these are not considered here" (Kremers, Rodrigues, Silveira, & da Silva Filho, 2010, p. 579); "Note however that 2 Hz is a harmonic of 1 Hz and may actually be a relevant spectral region to consider (albeit outside the scope of this report)" (Kosem, Gramfort, & Van Wassenhove, 2014, Figure S2; evident in figures but not discussed or included in analyses: Schettino, Porcu, Gundlach, Keitel, & Müller, 2020;Eidelman-Rothman et al, 2019;Chadnova et al, 2018;Winawer et al, 2013;Hönegger et al, 2011;Katzner et al, 2009;Pastor, Artieda, Arbizu, Valencia, & Masdeu, 2003;Pastor et al, 2002;Kaspar, Hassler, Martens, Trujillo-Barreto, & Gruber, 2001;Müller et al, 1998), preventing a wide-scale review.…”
Section: Higher Harmonicsmentioning
confidence: 99%
“…Unfortunately, most studies do not report whether or not there were responses at higher harmonics, as mentioned above. Moreover, when higher harmonic responses were reported to be present, they were often not described, for example, "Peaks were also present at the harmonics of the stimulus frequency but were not analyzed in this study" (Srinivasan et al, 1999, p. 5438); "Higher harmonics may play a role, especially at lower temporal frequencies (see, for example, the double peaks in the 12-Hz data in Figure 1), but these are not considered here" (Kremers, Rodrigues, Silveira, & da Silva Filho, 2010, p. 579); "Note however that 2 Hz is a harmonic of 1 Hz and may actually be a relevant spectral region to consider (albeit outside the scope of this report)" (Kosem, Gramfort, & Van Wassenhove, 2014, Figure S2; evident in figures but not discussed or included in analyses: Schettino, Porcu, Gundlach, Keitel, & Müller, 2020;Eidelman-Rothman et al, 2019;Chadnova et al, 2018;Winawer et al, 2013;Hönegger et al, 2011;Katzner et al, 2009;Pastor, Artieda, Arbizu, Valencia, & Masdeu, 2003;Pastor et al, 2002;Kaspar, Hassler, Martens, Trujillo-Barreto, & Gruber, 2001;Müller et al, 1998), preventing a wide-scale review.…”
Section: Higher Harmonicsmentioning
confidence: 99%
“…Here, we expect to find the opposite: because attentional stability should degrade with time-on-task, resulting in more variability in the timing of stimulus processing, theta ITPC should decrease. Although to our knowledge no studies have specifically examined time-on-task effects, earlier studies have reported that fatigue (resulting from sleep deprivation) may decrease theta ITPC (Eidelman-Rothman et al, 2018;Hoedlmoser et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The stronger ITPC to UFVs reflects better temporal synchronization of brain responses to UFVs and therefore supports the notion of a transient window for information processing. That is, stimulus-induced phase modulations have been suggested to promote information processing and transmission in the cortex (Canavier, 2015;Lakatos et al, 2013;Voloh and Womelsdorf, 2016) and increased ITPC values have been associated with better cognitive performance (Hanslmayr et al, 2005;Eidelman-Rothman et al, 2019) and enhanced attention (Joon Kim et al, 2007) during wakefulness. Importantly, the narrower peak for the evoked KCs following UFVs (Fig.…”
Section: Discussionmentioning
confidence: 99%